Viscoelastic testing to assess the effects of rapid fibrinogen concentrate administration after cardiopulmonary bypass: insights from the REPLACE study. Issue 6 (September 2021) - Rahe-Meyer, Niels; Levy, Jerrold H.; Ueda, Yuichi; Schmidt, Dirk Steffen; Gill, Ravi
Abstract : N/A: Haemorrhage during and following surgery results in increased morbidity and mortality. Low plasma fibrinogen levels have been associated with increased blood loss and transfusion requirements. Fibrinogen supplementation has been shown to reduce bleeding in coagulopathic patients. This post hoc study evaluated fibrinogen repletion and pharmacokinetic data from the REPLACE study. One hundred and fifty-two adult patients undergoing elective aortic surgery requiring cardiopulmonary bypass (CPB) with defined bleeding of 60–250 g at first 5 min bleeding mass were included in the phase III trial. Patients were randomized to receive either fibrinogen concentrate (FCH) or placebo following CPB removal. Plasma fibrinogen levels and viscoelastic testing parameters (ROTEM-based FIBTEM and EXTEM assays) were measured before, during, and after study treatment administration. A mean dose of 6.3 g FCH was administered in the FCH group, with a median infusion duration of 2 min. Immediately following completion of FCH administration, a rapid increase in plasma fibrinogen levels to near baseline (median change from baseline −0.10 g/l) was seen in the FCH group but not in the placebo group (median change from baseline −1.29 g/l). FCH administration also caused an immediate increase in FIBTEM maximum clot firmness (MCF) to 23 mm and improvements in EXTEM coagulation time and clot formation time by the end of infusion. There was a strong correlation between the plasma fibrinogen level and FIBTEM MCF. Treatment with high doses of FCH with a rapid infusion time resulted in immediate recovery to baseline levels of plasma fibrinogen and viscoelastic testing parameters.